Deteksi Keretakan Pada Pipa Menggunakan Sinyal Suara Dan Dual Mikrofon - Suhardi Panjaitan; Feblil Huda (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Piping system is used for fluid distribution in various fields of industry. When compared to other transportation systems such as vehicles, piping systems have a higher level of integration and are more effective. The need for pipeline is increasing in the industrial sector. Therefore, various types of damage that can occur in the pipeline system are important to be assessed and prevented. Detection of pipe damage is very important to prevent various losses and work accidents. Pipe damage in the form of crack is a problem that often occurs in pipe systems. In this study, the detection of damage to the pipe is done using sound signals and dual microphones. The sound signal method is an intelligent structural health monitoring that can prevent damage at a lower cost. Sound excitation was generated by loadspeaker and the response of the sound signal is sampled using dual microphones. Sound signal data from dual microphones is processed using wavelet transforms. From the experimental results it was found that the greatest wavelet coefficient of the microphone position is estimated to be the polar position of the damage. Keywords: Sound signal, dual microphones, crack, wavelet transform